2008
DOI: 10.1267/ahc.08004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Growth of Small Intestinal Epithelium by Adrenalectomy in Weaning Rats

Abstract: Functional maturation of the small intestine occurs during the weaning period in rats. It is known that this development is facilitated by glucocorticoid. However, the effect of glucocorticoid on morphological development of small intestine has yet to be clarified. The present study evaluated the morphological development and cell proliferation of the small intestine in adrenalectomized (ADX) rat pups. To further understand the mechanism of glucocorticoid effects on intestinal development, we examined the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…On the other hand, the higher expression of the gene for GRs in the proximal segment suggests that signaling through this receptor probably is the dominant factor in the upregulation of the expression of pIgR in this region. Taking into account that GC hormones influence a variety of epithelial cell functions in the small intestine by binding to the cytoplasmic GR [44,45], we pose that the higher expression of glucocorticoid receptors in epithelial cells of the proximal segment is an important factor in the higher level of pIgR expression at this site. Finally, food antigens and nutrients, such as vitamin A, abundant in the proximal small intestine, probably contribute to the higher expression of pIgRs in this segment as well [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the higher expression of the gene for GRs in the proximal segment suggests that signaling through this receptor probably is the dominant factor in the upregulation of the expression of pIgR in this region. Taking into account that GC hormones influence a variety of epithelial cell functions in the small intestine by binding to the cytoplasmic GR [44,45], we pose that the higher expression of glucocorticoid receptors in epithelial cells of the proximal segment is an important factor in the higher level of pIgR expression at this site. Finally, food antigens and nutrients, such as vitamin A, abundant in the proximal small intestine, probably contribute to the higher expression of pIgRs in this segment as well [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, HC treatment of suckling rats increases galactosylation and fucosylation of glycoproteins, which are biochemical markers associated with cellular maturation in the small intestine (4). In addition, the suppression of glucocorticoid secretion by adrenalectomy reduces the level of glycosylation in the small intestine at weaning (22); in vitro, HC induces functional alterations in rat enterocytes, including growth arrest, tight junction formation, microvilli maturation, and reorganization of the endoplasmic reticulum and trans-Golgi network (26). In human studies, Arsenault and Ménard (2) have shown that HC exhibits effects on differentiation and proliferation of fetal small intestinal organ culture, such as brush-border membrane hydrolytic activities (sucrase, lactase, glucoamylase, trehalase, and alkaline phosphatases) and epithelial cell proliferation.…”
mentioning
confidence: 99%
“…Maturation and maintenance of the intestinal epithelial barrier GC mediated effects on the maturation of the small intestine are well recognized both in rodents and humans [47]. For instance, adrenalectomy in rats during the weaning period impairs the mor phological development of the small intestine [48], while injection of cortisone or hydrocortisone to suckling rats increases the expres sion and activity of many small intestinal maturation markers [49 51]. The development of a human intestinal xenograft model demonstrated the responsiveness of the human small intestine to cortisone during the maturation period [52,53].…”
Section: Function and Roles Of Intestinal Gcsmentioning
confidence: 99%